Laughing Yoga for Hypertensive Elderly in Balinese Village, Indonesia - Ni Luh Gede Linda Ariasih; I Wayan Artana; Putu Wira Kusuma Putra (Journal of Advanced Nursing and Health Systems Innovation, 2026)
Background – The aging process in elderly leads to the alleviation of cardiovascular function, which contributes to the hypertension. Hypertension in the elderly poses a risk of serious complications if not properly managed. In addition to pharmacological therapy, non-pharmacological approaches such as laughter yoga have increasingly been implemented as complementary therapy. However, elderly participation in laughter yoga therapy is influenced by various factors that need to be explored in depth to understand their reasons and motivations for engaging in the therapy. Objective – This study aims to explore the reasons why elderly individuals with hypertension participate in laughter yoga therapy. Methods – This study employed a qualitative approach using a phenomenological method. 16 participants were involved, included elderly individuals with hypertension who participated in laughter yoga, family members, and village administrators. Data were collected through in-depth interviews and document analysis, such as identity cards and family registration cards. Data were analysed using the Miles and Huberman model, which includes data collection, data reduction, data display, and conclusion drawing. Data saturation was achieved at the tenth elderly participant, when no new themes emerged, and was confirmed with additional interviews. Trustworthiness was ensured through member checking, reflexive journaling, and source triangulation. Results – The reasons elderly individuals with hypertension participated in laughter yoga were categorized into internal and external factors. Internal factors included physical pain or discomfort, emotional condition, and the need for social interaction. External factors included motivation from the yoga instructor and support from family members. Conclusion – This study illustrates that laughter yoga is not only perceived as a physical therapy but also as a means of fulfilling the emotional and social needs of the elderly. These findings may serve as a basis for developing promotive and preventive programs to increase the participation of elderly individuals with hypertension in non-pharmacological therapies.